(untitled) - Riley, Dohn (Tahoe City, CA, 2001)
Alternative Energy Institute, Inc, (AEI) is a nonprofit, educational organization dedicated to informing the public about the upcoming non-renewable fuel crisis. AEI's revolutionary new book, "Turning the Corner: Energy Solutions for the 21st Century" presents the latest information about new energy research, both conventional and exotic, written in clear, straight-forward and compelling text. The energy field changes quickly, and, in order to keep pace with it, AEI has coupled this book with a portion of its website in order to provide the reader with the latest developments. The book covers the possibilities of energy conservation and efficiency, as well as renewable energy resources, but is also focused on potential emerging energy and propulsion technologies that may be developed in the 21st Century. This 385-page book is completely footnoted with Internet links and print media sources for the reader interested in delving deeper into the new energy field or relevant topics. Chapters include: "Cold Fusion: Fact or Fiction?", "Zero-Point Energy: Sailing the Sea of Energy," and "Universal Forces: Blackholes, Electrogravitics, & Deep Space Propulsion." This is a very exciting and well-researched book, one that AEI believes is long overdue.
Keywords: Renewable energy sources,Năng lượng tái sinh